2021
DOI: 10.1093/biolre/ioab124
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral smoking and developmental outcomes: a review of publications from a population birth cohort

Abstract: The adverse effects on the child of maternal smoking in pregnancy is well-recognised, but little research has been carried out on the possible non-genetic effects of ancestral smoking prior to the pregnancy including parental initiation of cigarette smoking in their own childhoods or a grandmother smoking during pregnancy. Here we summarise the studies that have been published mainly using data from the Avon Longitudinal Study of Parents and Children (ALSPAC). We demonstrate evidence that ancestral smoking pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…We have taken grandparent smoking and traumatic events in their childhoods as our exemplars of possible environmental factors that might have such an effect, since there is evidence that these exposures to grandparental ancestors have been associated with different outcomes in their grandchildren. For example, grandmothers' smoking during pregnancy has been demonstrated to be associated with several different outcomes in the grandchildren [6]; early onset of regular smoking of the grandparent prior to conception is associated with obesity in the grandchild [12], and a grandparent's exposure in midchildhood to famine is associated with long-term survival and improved mental health in their grandchildren [13,14]. We hypothesised that if there was a relationship between religious belief in the grandchildren and exposures of grandparents to environmental factors, the associations would be likely to be associated differently according to the sex of the index grandchild as well as of the type of grandparent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have taken grandparent smoking and traumatic events in their childhoods as our exemplars of possible environmental factors that might have such an effect, since there is evidence that these exposures to grandparental ancestors have been associated with different outcomes in their grandchildren. For example, grandmothers' smoking during pregnancy has been demonstrated to be associated with several different outcomes in the grandchildren [6]; early onset of regular smoking of the grandparent prior to conception is associated with obesity in the grandchild [12], and a grandparent's exposure in midchildhood to famine is associated with long-term survival and improved mental health in their grandchildren [13,14]. We hypothesised that if there was a relationship between religious belief in the grandchildren and exposures of grandparents to environmental factors, the associations would be likely to be associated differently according to the sex of the index grandchild as well as of the type of grandparent.…”
Section: Discussionmentioning
confidence: 99%
“…This often involves processes whereby environmental exposures to previous generations contribute to outcomes in unexposed descendants. For example, smoking (particularly pre-pubertal onset of regular smoking in grandfathers and prenatal smoking in grandmothers) has been shown to be associated with outcomes in grandchildren as varied as obesity, asthma, and autistic traits [6,7,8,9,10]. In general, such outcomes have been marked by a changing prevalence over time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses have stressed the importance of the timing of exposures in regard to outcomes in succeeding generations. We have shown this in regard to exposures in utero as well as in the pre-puberty period, with apparent effects on outcomes as diverse as autistic traits, myopia, obesity and IQ [Golding et al 2021]. Here we have demonstrated an association with an exposure to cigarette smoking in the adolescent period and suggest that this period of time should also be considered in further multi-generational studies.…”
Section: Discussionmentioning
confidence: 57%
“…However, this study also showed an adjusted association between fat mass of the offspring and maternal onset of smoking during adolescence (i.e. at ages [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%